Evaluation of hygiene conditions in commercial restaurants located in the North Zone of Rio de Janeiro (Research, Society and Development, 2020)
Several factors contributed to the increase in food consumption out of home and boosted the growth of commercial restaurants, a segment that should offer meals with adequate quality. In this study the hygienic-sanitary conditions of commercial restaurants located in the North Zone of Rio de Janeiro were evaluated. Nineteen establishments were analyzed through a checklist with 70 items, based on current legislation, which included six thematic blocks. Through the degree of compliance, restaurants were classified according to sanitary risk, being considered satisfactory (76 to 100%), regular (51 to 75%) or unsatisfactory (0 to 50%). From all the restaurants evaluated, the results showed that only 42% of commercial establishments were classified as having satisfactory sanitary risk, followed by the majority with 47% with regular sanitary risk and 11% with unsatisfactory sanitary risk. The main non conformities found in the establishments were irregular infrastructure, inappropriate behavior of food handlers, lack of monitoring of temperature, as well as the absence of a manual of good practices and standardized operational procedures. Taking these results into account, it is recommended that good practices be reviewed and implemented to guarantee the production of safe food for the consumer's health.